2008
DOI: 10.1364/ol.33.001273
|View full text |Cite
|
Sign up to set email alerts
|

Light-extraction enhancement of vertical-injection GaN-based light-emitting diodes fabricated with highly integrated surface textures

Abstract: We report on the fabrication of high-efficiency vertical-injection GaN-based light-emitting diodes (LEDs) fabricated with integrated surface textures. An optical ray-tracing simulation shows that the high integration of surface textures can effectively enhance the light-extraction efficiency. The integrated surface textures are fabricated on the top surface of LEDs by generating hexagonal cones on the periodically corrugated surfaces of n-GaN. Compared to reference LEDs without textures, LEDs fabricated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…The experimental data matches well with the improvement predicted by simulation using ray tracing method, which predicted ~ 1.5×. Variation of the photon extraction improvement is possibly due to varied pyramids' size and density, as suggested in [2]. After roughening, the devices were encapsulated in a dome shaped material.…”
Section: Device Performance and Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…The experimental data matches well with the improvement predicted by simulation using ray tracing method, which predicted ~ 1.5×. Variation of the photon extraction improvement is possibly due to varied pyramids' size and density, as suggested in [2]. After roughening, the devices were encapsulated in a dome shaped material.…”
Section: Device Performance and Analysissupporting
confidence: 81%
“…In addition, only a small fraction of those photons actually reaching the exit surface will escape due to the relatively large refractive index difference between AlN and air resulting in a narrow escape cone. Intensive efforts including surface roughening [2], photonic crystal [3], reflector [4] with high reflectivity and encapsulation [5] have contributed to substantially increasing the photon extraction efficiency in visible LEDs. Similar improvements could be expected with ultraviolet LEDs but the techniques will need to be adjusted to accommodate constraints imposed by the shorter wavelength compared to visible LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…3(a). It reveals that the textured surface with curved protrusions and hexagonal cones obtained from the proposed two-step roughening scheme could effectively improve the probability of photons escaping from semiconductor to air [8,15]. …”
Section: Resultsmentioning
confidence: 97%
“…Vertical-structure GaN-based LEDs (abbreviated as VLEDs) based on the transfer of sapphire substrate to a metal or semiconductor substrate have recently shown being very favorable for improving light output, efficiency, thermal conductivity, and power capability of GaN-based LEDs [4][5][6][7]. However, VLEDs with flat surface may suffer from low extraction efficiency because of the total internal reflection (TIR) effect [8]. According to Snell's law, the critical angle for a photon to escape from GaN (with a refractive index n~2.5) to air is about 23 o , suggesting a light extraction ratio from the surface is as low as 4% [9].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] It has also been found that introduction of light scattering elements to the surface of the LED enhances the performance. [10][11][12][13][14] Most of the theoretical and computational research on LED optics 10, 15-17 has relied on Monte Carlo raytracing simulations. Although the ray tracing simulations predict quantitatively e.g.…”
Section: Introductionmentioning
confidence: 99%